Determinant of Social Media Usage on Organization: Analysis of Millennial Employee of Telecommunication Company in Surabaya - Prihananto, Prahardika; Persada, Satria Fadil; Larasati, Intan Kartika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2022)
The urge to get in touch with others efficiently makes social media cannot be separated from people's lives nowadays. Moreover, the relationship between technological advancement and widespread usage of social media are pertinent to millennials who are big consumers of technology and digital natives. On the other hand, millennials are quite influential in Indonesia because most of the active workers in Indonesia are millennials. Therefore, the main focus of this research is analyzing the effect of social media usage by millennial employees on the corporate organization of one Telecommunication Company in Surabaya as its business is related to social media. This study utilizes the Structural Equation Modelling (SEM) approach using the Technology, Organization, and Environmental (TOE) Framework. The result shows that technology and environmental factors have a significant positive effect on social media usage, which offers a positive significant influence on the corporate organization